Probity in TCE: The case of the internal oversight structures at the United Nations - Da Veiga, M. R.; Maria, Major (9th Asia-Pacific Interdisciplinary Research in Accounting (APIRA) Conference, 2019)
Purpose: This paper provides ethics analysis of decisions regarding the UN internal oversight governance structures focused on Transaction Costs Economics (TCE) theory. Design/methodology/approach: We explore “probity” and “independence” transactions’ attributes through historical narrative case based research to answer to the questions – Why did decisions to change internal oversight structures were taken always in the aftermath of serious breaches of “probity”? How were “probity” hazards relieved? Findings: Our analysis shows that, at the UN, governance structures, i.e. incentives, did not relieve probity/ethics hazards as predicted in TCE (Williamson, 1999). A significant ethical conflict is therefore exposed, deontological versus teleological, latent between the ethics of the professional practice and the ethics of the executive power whenever the “independence” of the internal oversight is at stake. Originality/value: We argue that TCE should be modified to include McCloskey’s “virtues ethics” (2006) behavioral dimension as a transaction costs’ reduction device and an explanatory framework for bureaucratic structures’ ethical failures abandoning the opportunism behavioral assumption.